Complicated pseudodiverticulosis of small intestine: a rare case report - M., Kamal Raj; Venkatachalam, V.; A., Manasa (International Surgery Journal, 2019)
Diverticular disease though being a common entity in large bowel is recently noted to occur more proximally as well. In the jejunum, the mucosal outpouchings, called as pseudo-diverticulae, occurs with an incidence of 0.5-1.5%.Diagnosed incidentally as majority of them remain asymptomatic. When they are symptomatic, dyspepsia and bloating, recurrent abdominal cramping, malabsorption and megaloblastic anemia occurs. On occasions it is not uncommon for patients to present with hemorrhage, infections, obstruction or perforation. Perforation, being a rare presentation occurs in less than 6% of the cases. We present a case of a 70 year old male, who presented as acute abdomen, found to have isolated jejunal diverticular perforation intraoperatively.